Pengaruh Social Media Marketing terhadap Purchase Intention dengan Moderasi Brand Trust pada Produk Fashion - Erica Agnes Yuliana; Dewi Pratiwi Indriasari (SENTRI: Jurnal Riset Ilmiah, 2026)
The development of social media and the competitive nature of the local fashion industry has prompted companies to implement effective marketing strategies to increase consumer purchasing intent. This study aims to analyse the influence of social media marketing, brand awareness, and consumer engagement on purchase intent, with brand trust as the moderating variable, for the local fashion brand Ecinos. The study used a quantitative approach, involving 140 Generation Z respondents from the Jabodetabek area who are active social media users and interested in Ecinos products. Data were collected through the distribution of questionnaires and analysed using Structural Equation Modelling-Partial Least Squares (SEM-PLS). The results of the study showed that social media marketing, brand awareness, and consumer engagement with the brand had a positive effect on purchase intention. These findings demonstrate that consumer trust in a brand is a key factor in enhancing the effectiveness of marketing strategies and encouraging consumer purchase intent. This study is expected to provide companies with a reference for developing more effective marketing strategies. Thus, building brand trust is crucial for local fashion brands to effectively convert digital marketing efforts into higher purchase intention among Generation Z consumers.